Literature Review: Comparison of the Quality of Papanicolaou, Giemsa, and May-Grunwald Giemsa Staining in Pleural Effusion Specimens - Nurhaliza, Winarti; Rahmawati, Yeni; Nailufar, Yuyun (LPPM STIKes Muhammadiyah Ciamis, 2025)
Pleural effusion is a pathological condition characterized by fluid accumulation in the pleural cavity, which can occur due to infection, malignancy, or systemic disorders such as congestive heart failure. Cytological examination is an effective diagnostic method for detecting abnormal cells and malignancy in pleural effusion by reviewing the quality of staining results. This study aims to analyze and compare the staining quality of Papanicolaou, Giemsa, and May Grunwald Giemsa in pleural effusion cytology examination. The literature review results included 8 journals that met the inclusion criteria. These journals were obtained from the Google Scholar, PubMed, and Publish or Perish databases using the PICO search method and then selected based on inclusion and exclusion criteria using the PRISMA flow diagram. The results of the literature review showed that the Papanicolaou method provided clearer contrast between the nucleus and cytoplasm with a good background, Giemsa displayed cell morphology but the background was less clean, while May-Grunwald Giemsa showed stable staining results and good cell detail.